2016
DOI: 10.1007/s10570-016-0887-0
|View full text |Cite|
|
Sign up to set email alerts
|

Dry, hydrophobic microfibrillated cellulose powder obtained in a simple procedure using alkyl ketene dimer

Abstract: In order to produce dry and hydrophobic microfibrillated cellulose (MFC) in a simple procedure, its modification with alkyl ketene dimer (AKD) was performed. For this purpose, MFC was solventexchanged to ethyl acetate and mixed with AKD dissolved in the same solvent. Curing at 130°C for 20 h under the catalysis of 1-methylimidazole yielded a dry powder. Scanning electron microscopy of the powder indicated loss in nanofibrillar structure due to aggregation, but discrete microfibrillar structures were still pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
(46 reference statements)
6
40
0
Order By: Relevance
“…Figure 1 shows the MNCC still maintained the crystalline structure the same as NCC. However, the modification can prevent agglomeration of fibers, resulting in a weak diffraction peak [ 28 ]. It can be clearly seen that the crystallization peak intensity of MNCC decreased in comparison to the natural NCC, indicating that important reactions had occurred on the NCC surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the MNCC still maintained the crystalline structure the same as NCC. However, the modification can prevent agglomeration of fibers, resulting in a weak diffraction peak [ 28 ]. It can be clearly seen that the crystallization peak intensity of MNCC decreased in comparison to the natural NCC, indicating that important reactions had occurred on the NCC surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…In paper sizing, at least some of the AKD can react with the cellulose chains on paper to form covalent bonds [ 35 , 36 ]. There has been recent interest in reacting AKD with different types of polysaccharides, e.g., microcrystalline cellulose [ 37 ], microfibrillated cellulose [ 38 , 39 ], cellulose nanofibers [ 40 , 41 ], bacterial cellulose [ 42 ], carboxymethyl cellulose [ 43 ], hydroxyethyl cellulose [ 44 ], starch [ 45 , 46 ], and cashew gum [ 47 ]. Thus far, the reaction of xylan with a ketene dimer has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Koppolu et al successfully used the roll-to-roll coating technique with noncontact infrared drying and air drying to coat CNF onto paper at speeds of 30 m/min [93]. In another work, it has been shown that by increasing the rod metering speed and the drying temperature, the thickness and the weight of the coating decrease; in addition, it has also been reported that the WVTR of polymer dispersion coatings decreases with the increase of the drying temperature of the coating [94,95].…”
Section: Coating Process and Storage Of Coated Materialsmentioning
confidence: 99%